유해물질 잔류조사 시스템 구축 - 한재환 (한국농촌경제연구원, 2009)
Residue survey on hazardous substances in agricultural products is divided into before and after agricultural shipments. While Ministry for Food, Agriculture, Forestry and Fisheries(MIFAFF) takes charge of the residue survey before agricultural shipments, Korea Food and Drug Administration(KFDA) manages it after agricultural shipments. National Agricultural Products Quality Management Service(NAQS) under MIFAFF has administered food safety inspection programs, which is initially introduced in 1994. Operating food safety inspection programs, NAQS performs the residue survey with the some quantity of the food safety inspection programs. Currently, the residue survey of NAQS is not achieved in the systematic process, and a regulatory-driven form. KFDA is in the process of building a system for residue survey on hazardous substances. Strictly speaking, a national residue survey on hazardous substances is not fulfilled yet in Korea. The main goal of this study is to develop an economic and efficient model for residue survey on hazardous substances in agricultural products. Major residue surveys on hazardous substances of U.S. are Pesticide Data Program(PDP) of United States Department of Agriculture(USDA) and Total Diet Study(TDS) of Food and Drug Administration(FDA). European Union(EU) runs EU co-ordinated monitoring program for residue survey. Both U.S. and EU possess of a very systematic and scientific system in the hazardous substances management. It is time to construct a national residue survey in Korea for an efficient and economic management of hazardous substances in agricultural products. Data produced in a national residue survey will be utilized in diverse sectors, including consumer and environmental groups, CODEX, government agencies, food and agribusiness companies, and academics. It is expected that results of a national residue survey are used as basic materials for risk assessment which makes it possible scientific agri-food safety management. Ultimately, a national residue survey will improve the level of safety management in agricultural products.
Keywords: 잔류조사